TINGKAT TUTUR RANAH KELUARGA PERNIKAHAN ANTAR BANGSA JEPANG DAN BALI - I Made Yawara Sumi Putra; Anak Agung Ayu Dian Andriyani; Ni Wayan Meidariani (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2023)
This research aims to analyze the function of speech acts in the dialogue of Japanese and Balinese intermarriage family and identify the type of speech level in speech acts contained in the results of Japanese and Balinese intermarriage family. The research uses the theory of sociopragmatics, supported by the theory of speech act function, another supporting theory is the theory of context. The methods and techniques of data collection used in the research are listening method and chap method followed by note-taking and classification techniques. The methods and techniques of data analysis used are qualitative descriptive methods. While the method and technique of presenting data analysis using informal methods. The results showed that in the Japanese and Balinese Intermarriage Family Spoken Level there are ten data of speech act functions consisting of, assertive speech act functions as much as two data, expressive speech act functions as much as three data, directive speech act functions as much as three data, and commissive speech act functions as much as two data, and five data of speech level types consisting of, three data of futsuugo speech level types, two data of teineigo speech level types.